2016
DOI: 10.4049/jimmunol.1600066
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Enhances IgE-Mediated Mast Cell Responses and Is Essential for the Development of Experimental Food Allergy in IL-10–Deficient Mice

Abstract: IL-10 is a key pleiotropic cytokine that can both promote and curb Th2-dependent allergic responses. Herein we demonstrate a novel role for IL-10 in promoting mast cell expansion and the development of IgE-mediated food allergy. Oral ovalbumin challenge in sensitized BALB/c mice resulted in a robust intestinal mast cell response accompanied by allergic diarrhea, mast cell activation, and a predominance of Th2 cytokines, including enhanced IL-10 expression. In contrast, the development of intestinal anaphylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 55 publications
7
69
1
Order By: Relevance
“…Interestingly, uninfected IL‐10 deficient mice exhibited less of a temperature drop after systemic allergen challenge (Figure B) than uninfected wild‐type mice (Figure C). This is consistent with two recent studies, one showing that IL‐10 can potentially enhance IgE‐mediated mast cell function and another demonstrating that the absence of IL‐10 is associated with reduced disease in a murine food allergy model . As we did not evaluate uninfected IL‐10 deficient and wild‐type mice in the same experimental trials, definitive determination of whether IL‐10 enhances systemic anaphylaxis will be a focus of future studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, uninfected IL‐10 deficient mice exhibited less of a temperature drop after systemic allergen challenge (Figure B) than uninfected wild‐type mice (Figure C). This is consistent with two recent studies, one showing that IL‐10 can potentially enhance IgE‐mediated mast cell function and another demonstrating that the absence of IL‐10 is associated with reduced disease in a murine food allergy model . As we did not evaluate uninfected IL‐10 deficient and wild‐type mice in the same experimental trials, definitive determination of whether IL‐10 enhances systemic anaphylaxis will be a focus of future studies.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we also investigated the requirement of IL‐10 in conferring protection against anaphylaxis. IL‐10 has been implicated as having both enhancing and suppressive effects on IgE‐mediated inflammation . Previously, our laboratory found that host IL‐10 production is responsible for helminth‐mediated suppression of basophil sensitivity to IgE‐mediated activation .…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to our observations, recent reports indicate that IL‐10 can enhance IgE‐mediated MC responses in vivo . However, the requirement of IL‐10 in the induction of IgE‐MC–dependent food allergic response appeared to be related to the capability of IL‐10 to alter MC proliferation and numbers . Previous studies by us and others have reported a requirement for small intestine (SI) MC expansion in IgE‐mediated, MC‐dependent food allergic responses in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…can enhance IgE-mediated MC responses in vivo. 64 However, the requirement of IL-10 in the induction of IgE-MC-dependent food allergic response appeared to be related to the capability of IL-10 to alter MC proliferation and numbers. 64 60,62 It is possible that a combinatory effect of decreased surface expression of FceRI and reduced IgE-FceRI signalling machinery may be required to drive the lack of responsiveness to IgE.…”
Section: Mcs Express Tlr Receptors Including Tlr-4 and Expression Andmentioning
confidence: 99%
“…149 The latter study reported IL10 upregulation as a potential mechanism for immunomodulation of the tumor microenvironment. This is especially interesting in light of recent studies from hypersensitivity research demonstrating that IL10 has pro-T H 2 inflammatory effects, 150,151 which are in contrast to IL10 being thought of as an immunosuppressive cytokine. Could IL10 application be utilized to enhance antitumor immune-system responses, specifically T-cell and innate lymphoid-cell programming?…”
Section: Cytokinesmentioning
confidence: 99%